Occupational ionising radiation and risk of basal cell carcinoma in US radiologic technologists (1983–2005). Issue 12 (8th September 2015) - Lee, Terrence; Sigurdson, Alice J; Preston, Dale L; Cahoon, Elizabeth K; Freedman, D Michal; Simon, Steven L; Nelson, Kenrad; Matanoski, Genevieve; Kitahara, Cari M; Liu, Jason J; Wang, Timothy; Alexander, Bruce H; et al.
Abstract : Objective: To determine risk for incident basal cell carcinoma from cumulative low-dose ionising radiation in the US radiologic technologist cohort. Methods: We analysed 65 719 Caucasian technologists who were cancer-free at baseline (1983–1989 or 1994–1998) and answered a follow-up questionnaire (2003–2005). Absorbed radiation dose to the skin in mGy for estimated cumulative occupational radiation exposure was reconstructed for each technologist based on badge dose measurements, questionnaire-derived work history and protection practices, and literature information. Radiation-associated risk was assessed using Poisson regression and included adjustment for several demographic, lifestyle, host and sun exposure factors. Results: Cumulative mean absorbed skin dose (to head/neck/arms) was 55.8 mGy (range 0–1735 mGy). For lifetime cumulative dose, we did not observe an excess radiation-related risk (excess relative risk/Gy=−0.01 (95% CI −0.43 to 0.52). However, we observed that basal cell carcinoma risk was increased for radiation dose received before age 30 (excess relative risk/Gy=0.59, 95% CI −0.11 to 1.42) and before 1960 (excess relative risk/Gy=2.92, 95% CI 1.39 to 4.45). Conclusions: Basal cell carcinoma risk was unrelated to low-dose radiation exposure among radiologic technologists. Because of uncertainties in dosimetry and sensitivity to model specifications, both our null results and our findings of excess risk for dose received before age 30 and exposure before 1960 should be interpreted with caution.